2023
DOI: 10.3390/ijms24044053
|View full text |Cite
|
Sign up to set email alerts
|

Genotoxicity of Novel Pyrazolo[4,3-e]tetrazolo[1,5-b][1,2,4]triazine Sulfonamides in Normal and Cancer Cells In Vitro

Abstract: Pyrazolo[4,3-e]tetrazolo[1,5-b][1,2,4]triazine sulfonamides constitute a novel group of heterocyclic compounds with broad biological activities including anticancer properties. The compounds investigated in this study (MM134, -6, -7, and 9) were found to have antiproliferative activity against BxPC-3 and PC-3 cancer cell lines in micromolar concentrations (IC50 0.11–0.33 µM). Here, we studied the genotoxic potential of the tested compounds with alkaline and neutral comet assays, accompanied by immunocytochemic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 51 publications
1
7
0
Order By: Relevance
“…In the initial in silico research, we performed molecular docking and molecular dynamics studies of the previously studied MM129 compound and the compounds investigated in the present work ( MM134 , -6 , -7 , and -9 ). We found that compounds may inhibit the molecular targets to a similar or greater extent than previously investigated MM -compounds (including MM129 ) [ 8 , 11 ]. However, these results were established with the use of single molecular docking and dynamics software.…”
Section: Resultsmentioning
confidence: 71%
See 4 more Smart Citations
“…In the initial in silico research, we performed molecular docking and molecular dynamics studies of the previously studied MM129 compound and the compounds investigated in the present work ( MM134 , -6 , -7 , and -9 ). We found that compounds may inhibit the molecular targets to a similar or greater extent than previously investigated MM -compounds (including MM129 ) [ 8 , 11 ]. However, these results were established with the use of single molecular docking and dynamics software.…”
Section: Resultsmentioning
confidence: 71%
“…The genotoxic activity of the compounds in the comet assay and γH2AX staining was also described. Furthermore, it was indicated that the DNA-damaging capability of the compounds may be attributed to the inhibition of CHK1 kinase, as indicated by in silico results [ 8 , 11 ]. Furthermore, these compounds exhibited profound pro-apoptotic activity in the BxPC-3 cell line following 24 and 48 h incubation of cells in vitro, where 2xIC 50 concentrations of all MM -compounds induced apoptosis of 68.1 ± 7.33% to 95.1 ± 1.48% of the cells [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations